4-H Pizza Garden: An Agricultural Adventure - Janet Golden; Joy Jordan; Nan Jensen; Betty Lipe; Millie Ferrer-Chancy; Anne Fugate; Erin Karkheck; Linda Bobroff; Karla Shelnutt; Tracy Tesdall (EDIS, 2014)
This curriculum was designed for educators to teach young people about where their food originates by using something children love to eat…PIZZA! According to a recent Gallup poll, kids between the ages of 3 and 11 prefer pizza to all other foods for lunch and dinner. Americans eat about 100 acres of pizza each day, or 350 slices per second! This 4-H in the Classroom project, originating in Pinellas County, Florida, was designed for grades 3–5, but can be adapted to serve other grade levels. The lessons cover subject areas such as mathematics, social studies, language arts, and science. It has been used in Pinellas County very successfully since 2000 by the 4-H Program in collaboration with their Florida Ag in the Classroom Initiative. This revised 89-page fact sheet was written by Janet Golden, Joy Jordan, Nan Jensen, Betty Lipe, Millie Ferrer, Anne Fugate, Erin Karkheck, Linda Bobroff, Karla Shelnutt, and Tracy Tesdall, and published by the UF Department of 4-H Youth Development, July 2014.